EDUCATION AND ECOLOGICAL CITIZENSHIP: TEACHING PRACTICES FOR QUILOMBOLA AND SERTANEJO SCHOOLS - da Silva, Manoel Messias (Seven Editora, 2025)
This chapter analyzes the relevance of education and ecological citizenship in quilombola and sertanejo contexts, highlighting how these territories broaden the meaning of Science teaching by integrating the Caatinga biome, local culture, and traditional knowledge as constitutive dimensions of the educational process. It argues that the school, by articulating scientific knowledge and community memory, becomes a strategic space for the development of critical awareness, social participation, and sustainable practices. Based on a comprehensive literature review, the chapter discusses the theoretical foundations of Ecological Citizenship, Critical Environmental Education, and the Ecology of Knowledge, while also examining the pedagogical practices of quilombola schools and the Pedagogy of Living Together in the Semiarid region. Finally, it highlights the convergences, tensions, and challenges involved in constructing a contextualized education committed to territorial preservation, the appreciation of traditional identities, and the formation of ecological subjects.DOI: https://doi.org/10.56238/sevened2025.038-061